PERLINDUNGAN BAGI WANITA TERHADAP TINDAK KEKERASAN - Tri Wahyu Widiastuti (Universitas Slamet Riyadi, 2008)
Abstract : Violence to the woment involve every violence based on different of sex which in cause lost or injury physical, sexual or phychological of woment, involve threat or robbery of independent in privat or public aspect. Cause of violence to the woment are poverty which cause violence as a cannal of frustration and aggression, instability of society cause of increase of sadism culture. Brutality is the part of society weapon which flaming because of war.Protection to the woment from brutality are give same role of woment and man at all aspect and empowering of woment Key word : Protection, woment, violence.